Gender, Social Value Orientation, and Tax Compliance - John D'Attoma; Clara Volintiru; Antoine Malezieux (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper brings an important empirical contribution to the academic literature by examining whether gender differences in tax compliance are due to higher prosociality among women. We conducted a large cross-national tax compliance experiment carried out in Italy, U.K., U.S., Sweden, and Romania, and assessed tax compliance as reported income as a percentage of total earned income in the experiment. We uncover that women declare a significantly higher percentage of their income than men in all five countries. While some scholars have argued that differences in honesty between men and women is actually being mediated by the fact that women are more prosocial than men, we find that women are not more prosocial than men in all countries. Furthermore, though overall women tend to be more prosocial on average than men, SVO has no mediation effect between gender and tax compliance. We conclude then that although differences in prosociality between men and women seem to be context dependent, differences in tax compliance are indeed much more consistent.
Keywords: A10; C90; C92; D64; H26; H30; H41; 330; behavioral economics; tax compliance; gender